2013
DOI: 10.2500/ajra.2013.27.3858
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Incidence and Susceptibility among Methicillin-Resistant Staphylococcus aureus Isolated from Intranasal Cultures Associated with Rhinosinusitis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…The acquired resistance of S. aureus has been the focus of several publications, especially after penicillin began to be used in the middle of the past century, regarding MRSA epidemiology and its resistance to penicillin. Transmission mainly occurs in hospitals ( 20 – 22 ). The excessive use of antibiotics in hospitals is considered a major risk in the guidelines of the Society for Healthcare Epidemiology of America (SHEA) ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The acquired resistance of S. aureus has been the focus of several publications, especially after penicillin began to be used in the middle of the past century, regarding MRSA epidemiology and its resistance to penicillin. Transmission mainly occurs in hospitals ( 20 – 22 ). The excessive use of antibiotics in hospitals is considered a major risk in the guidelines of the Society for Healthcare Epidemiology of America (SHEA) ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it was found that P128 was not only effective against MSSA isolates, but also maintained efficacy when tested against an MRSA sinus‐derived clinical isolate. Rates of MRSA in CRS have been seen to be as high as 26% in 2010, with the trend of MRSA isolation increasing . Further, it has been noted that high nasal burden of MRSA is linked with an increased risk of developing invasive infection and is a reservoir for bacteraemia .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the incidence of Staph. aureus positive cultures amounts to 7.7% and the one of MRSA positive cultures to 1.06% [ 58 ].…”
Section: Epidemiology Of Chronic Rhinosinusitis and Their Subtypesmentioning
confidence: 99%
“…aureus in 19% of the patients with CRS [ 62 ]. Among those, 19% were MRSA so that in this context the incidence of MRSA in CRS is relatively stable with 3.8% of the CRS patients in the last years [ 58 ]. However, those data are not confirmed.…”
Section: Epidemiology Of Chronic Rhinosinusitis and Their Subtypesmentioning
confidence: 99%